Determinants of Loan Loss Provisions in Chinese Banking - ZHENG, BIYING (2017)
The economy in China has developed rapidly since the reform and opening in 1987. Recently, especially after the financial crisis in 2008, the growth of the economy has slowed down. As the main channel of financing in China is indirect financing, banks credit has already taken up 80% of financial market. According to the report which China Banking Regulatory Commission (CBRC) published in 2016, Chinese commercial banks’ impaired loan is 1.53 trillion RMB. The problem of non-performing loans is becoming increasingly severe.